Analysis of Price, Product Quality and Location on Purchasing Decisions (Case Study at D'Top Chicken & Burger, Responsibility Branch) - Barkah, Dwi Ariyanti; Dewi Mulyani, Indah; Ernitawati, Yenny; Afridah, Nur (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
D'Top Chicken & Burger is a franchise business operating in the fast food sector that sells processed food products. Made from fried chicken, it can be combined with other menus. This study aims to analyze the effect of price, product quality and location on purchasing decisions and what factors influence purchasing decisions at D'Top Chicken & Burger, Keuntungan Branch. The approach used in this research is a quantitative approach. Data collection techniques were carried out using observation, interviews, questionnaires, documentation and literature study. The sample determination technique used nonprobability sampling, with incidental sampling, obtaining 100 respondents. The statistical analysis techniques of this research include validity test, reliability test, classic assumption test, t test, F test, coefficient of determination (R2), and multiple linear regression analysis with the help of SPSS. The results in this study show that price has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, location has a negative and insignificant effect on purchasing decisions. D'Top Chicken & Burger, Kenggungan Branch, pays more attention to places of business such as expanding parking lots and supporting infrastructure to create a sense of comfort.